2014
DOI: 10.1016/j.compgeo.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of small variations in fracture geometric characteristics on peak rock mass properties at a mining project using a coupled DFN–DEM approach

Abstract: Using field data from Agnico-Eagle's Meliadine gold project located in Nunavut Territory in northern Canada, a coupled DFN-DEM approach was used to evaluate the rock mass mechanical properties at REV. Variability in the structural data gathered on site and the variability associated with the stochastic modeling process have an impact on discrete fracture model (DFN) properties. Through a sensitivity analysis, this paper assesses the influence of a variation in the DFN model input parameters' values on the rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…By testing the SRM specimens, the failure mechanisms of rock mass can be observed in detail and mechanical properties such as the strength, stiffness and brittleness of a rock mass can be estimated. The SRM approach has been successfully utilized for evaluating rock mass mechanical properties of site specific cases Cundall et al, 2008;Esmaieli et al, 2010;Grenon et al, 2014;Mas Ivars et al, 2011;Pettitt et al, 2011;Pierce et al, 2007;Vallejos et al, 2013;Vallejos et al, 2014;Zhang et al, 2011), and also the effects of pre-existing discontinuities on rock mass behaviour (Bahaaddini et al, 2013;Chiu et al, 2013;Lambert and Coll, 2014;Pan et al, 2014;Scholtès and Donzé, 2012). For Coal Measures, Deisman et al (2010) used the SRM approach to investigate the effects of fractures or joints on the geomechanical properties of coal and showed that the SRM method is capable of simulating the strength and deformation of a coal seam.…”
Section: Introductionmentioning
confidence: 99%
“…By testing the SRM specimens, the failure mechanisms of rock mass can be observed in detail and mechanical properties such as the strength, stiffness and brittleness of a rock mass can be estimated. The SRM approach has been successfully utilized for evaluating rock mass mechanical properties of site specific cases Cundall et al, 2008;Esmaieli et al, 2010;Grenon et al, 2014;Mas Ivars et al, 2011;Pettitt et al, 2011;Pierce et al, 2007;Vallejos et al, 2013;Vallejos et al, 2014;Zhang et al, 2011), and also the effects of pre-existing discontinuities on rock mass behaviour (Bahaaddini et al, 2013;Chiu et al, 2013;Lambert and Coll, 2014;Pan et al, 2014;Scholtès and Donzé, 2012). For Coal Measures, Deisman et al (2010) used the SRM approach to investigate the effects of fractures or joints on the geomechanical properties of coal and showed that the SRM method is capable of simulating the strength and deformation of a coal seam.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, building upon experiments and theoretical analyses, numerous researchers have employed numerical methods to construct computational models of fractured rock masses and carry out relevant numerical mechanical tests. For example, the equivalent rock mass technology, which combines a three-dimensional fracture network simulation technique and discrete element platform, has been extensively employed in the construction of fractured rock mass models at both indoor and engineering scales [7][8][9][10][11][12]. Meanwhile, the parameters of the equivalent rock masses, such as stiffness, deformation modulus, Poisson's ratio, internal friction angle, trace length, and fracture aperture, have also been adopted to estimate the REV size of fractured rock masses [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer technology, numerical simulation methods mainly include finite element method (FEM), finite difference method (FDM), boundary element method (BEM), discrete element method (DEM), back Analysis, lagrangian analysis are often used in research. And the rise of discrete fracture network (DFN) technology makes the simulation effect is closer to the practical condition [18][19][20][21]. DEM, combined with theoretical calculation or model test, can be used to predict the hydraulic pressure behind the lining, surrounding rock deformation, and support parameters under different conditions during the design stage [22][23][24][25][26][27][28][29][30], so as to make reasonable support design to reinforce the surrounding rock of the tunnel and avoid the occurrence of disasters [14,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%